Developing a Model License: A Canadian Consortium's Experience - Gilllies, Scott; Horava, Tony (Université d'Ottawa | University of Ottawa, 2009)
The authors describe the process of drafting a model electronic resources license for the OCUL (Ontario Council of University Libraries) consortium in Ontario, Canada. The features, purposes, and benefits of model licenses are discussed. The authors describe the process that was involved, and some of the key issues and challenges in relation to OCUL's mission and values. The future of model licenses is discussed in relation to the evolving educational, technological, financial and legal issues affecting libraries.
Keywords: model license; OCUL; Canada; purposes; process; benefits